Evaluation of deflection–creep properties of sleeve-retrofitted pultruded glass fiber reinforced polymer composite cross-arms for transmission tower applications - Sukumaar, Vijayvignesh Namasivayam; Ishak, Mohamad Ridzwan; Abdullah, Mohd Na’Im; Mohd Zuhri, Mohamed Yusoff; Muhammad Rizal, Muhammad Asyraf (Korean Fiber Society, 2025)
Pultruded glass fiber-reinforced polymer composite is used for cross-arm constructions. This research focusses on creep response and deflection behavior using cantilever test conditions. The behavior of structurally strengthened cross-arms is evaluated under both short-term and creep scenarios to understand how structural installation affects their performance. By applying Findley’s power law, it is ascertained that this empirical method can replicate the cross-arm’s viscoelastic response. The outcomes demonstrate the effect of sleeve structures in decreasing the deflection and increasing the resistance to bending forces. Point Y3 exhibited the largest strain according to long-term creep testing, but the reinforced cross-arm showed better resistance. This observation proves that the point Y3 endures the highest stress during operation thereby becomes the point of initial of rupture. Experimental results show an enhancement by the addition of sleeve retrofit under instantaneous and long-term static loading conditions by about 28.50% and 23.50% respectively. Life span prediction showed that both the variants had a notable decline in average elastic modulus over 50-year period, with the upgraded version being about 50% stronger with the corresponding increase in reduction factor by a value of 0.21. As a result, this analysis confirms that the sleeve-retrofitted composite cross-arms possess superior creep capabilities and confine to feasible installations for such applications. The generalized equation for the prediction of the effective utilization of the cross-arm based on the Findley numerical model had been established.